Current Status and Future Perspectives of Gene Therapy for Heart Failure - Yuting Zhai; Yang Liu; Dongye Li (International Journal of Heart Research, 2018)
Heart failure(HF) is a disease with high morbility and mortality. The benefits of current pharmacological and device therapy for survival outcomes of patients with HF are limited. Gene therapy represents a novel promising strategy in treating HF, as it can theoretically normalize the aberrantly expressed genes and their regulatory mechanisms permanently. However, the translation of gene therapy for HF from bench to bedside has been less successful. There are many challenges ahead for gene therapy, especially in the areas of selection of the optimal targets, the needs for developing delivery systems and the improvement in design of clinical trials. In this review, we summarize the most promising gene targets which have been used in experimental and clinical studies for treating HF, highlighting the results from several clinical trials. We also review the latest development in gene therapy vectors and delivery methods, aiming to provide directions for future studies.
Keywords: Heart failure